Alluvium : Dhaka, Bangladesh in the crossroads of water - Kieran, Stephen, 1951-; Timberlake, James, 1952- (2015)
Since 2007, architects Stephen Kieran and James Timberlake have directed a design-research laboratory on Dhaka for graduate students at the University of Pennsylvania School of Design. What began as a desire to help a city in need became an immersion in investigating its ebbs and flows, mapping its urban systems, and charting its development via annual visits. The result of this extended study is Alluvium: Dhaka, Bangladesh, in the Crossroads of Water, a cross-genre book that incorporates diverse media and layers of narrative and analysis to encourage new readings and perspectives. The book includes first-person narratives by architects and planners, documentary photographs, and maps and infographics that visually represent the intricate connections between people, water, land, and health in this delta megacity. The work proposes a new approach to understanding place that is interwoven with human interest--an intimate, collaborative, research-based model that holds relevance for both the developing and developed worlds.
Preface : toward an architecture of empathy -- Beginning : a renewed research agenda -- Telling : textual sketches of Dhaka / by eleven Western architects and planners -- Looking : images of daily life in the densest megacity on Earth -- Analyzing : delta/water/land/people/health : urban systems maps, fact indices, and infographics -- Acting : meaningful intervention -- Afterword : Dhaka 2040 : a vision for the future.
"Extracts from seven years of the Dhaka Design-Research Lab at the University of Pennsylvania School of Design."
Includes bibliographical references (pages 346-349).
Keywords: City planning -- Bangladesh -- Dhaka; Architecture -- Bangladesh -- Dhaka; Architecture and society -- Bangladesh -- Dhaka; Architecture; Architecture and society; Buildings; City planning; Dhaka (Bangladesh) -- Buildings, structures, etc; Bangladesh -- Dhaka